2013
DOI: 10.1123/ijspp.8.2.195
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Methods to Quantify the In-Season Training Load of Professional Soccer Players

Abstract: Purpose:To compare various measures of training load (TL) derived from physiological (heart rate [HR]), perceptual (rating of perceived exertion [RPE]), and physical (global positioning system [GPS] and accelerometer) data during in-season field-based training for professional soccer.Methods:Fifteen professional male soccer players (age 24.9 ± 5.4 y, body mass 77.6 ± 7.5 kg, height 181.1 ± 6.9 cm) were assessed in-season across 97 individual training sessions. Measures of external TL (total distance [TD], the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

31
221
2
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(262 citation statements)
references
References 23 publications
31
221
2
8
Order By: Relevance
“…In sports games, we still consider the determination of the load by measuring the heart rate a relatively accurate method that provides us with the relevant information required. Scott et al (2013), who found a correlation (p < 0.01) with multiple indicators of the external load (along with the distance covered), confirmed this in the study.…”
Section: Introductionsupporting
confidence: 77%
“…In sports games, we still consider the determination of the load by measuring the heart rate a relatively accurate method that provides us with the relevant information required. Scott et al (2013), who found a correlation (p < 0.01) with multiple indicators of the external load (along with the distance covered), confirmed this in the study.…”
Section: Introductionsupporting
confidence: 77%
“…Average training duration (77 min), total distance (5614 m), running (591 m) and high-speed running (203 m) were high in the range of, or even somewhat higher than, what other teams demonstrated (65-76 min, 3898-5667 m, 220-412 m and 41-205 m, respectively) (Akenhead et al, 2016;Scott et al 2013;Malone et al 2015;Anderson et al 2016). To date, as far as we are aware, no other studies have reported the number of accelerations or A typical week with 1 match (A) was considered to be a week starting with a recovery training for the starters (not recorded) and a nonstarters training session for the nonstarters (MD+1), followed by a day off, 4 subsequent training sessions (MD-4, MD-3, MD-2 and MD-1) and a match (only for starters).…”
Section: Discussionmentioning
confidence: 99%
“…To fairly compare our data with other studies that assessed the in-season training load of full sessions in top-level leagues of professional football (Akenhead et al, 2016;Scott et al 2013;Malone et al 2015;Anderson et al 2016), we used the averages of the 4 training days in our study. Average training duration (77 min), total distance (5614 m), running (591 m) and high-speed running (203 m) were high in the range of, or even somewhat higher than, what other teams demonstrated (65-76 min, 3898-5667 m, 220-412 m and 41-205 m, respectively) (Akenhead et al, 2016;Scott et al 2013;Malone et al 2015;Anderson et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have observed the relationship between session RPE and external loads measured using GPS technology. 3,8 These studies have reported significant correlations between session RPE and both GPS and accelerometer derived variables (r = 0.71-0.84; P < 0.01).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, additional methods may be required to assess session RPE as a global estimate of training load during soccer training. 4,5,8 A Global Positioning System (GPS) is a space-based navigation system that provides location and time information 9 . GPS technology has improved over the last several years 9 and evidence indicates that GPS data can provide a viable estimate of external training loads imposed on athletes in team sports.…”
Section: Introductionmentioning
confidence: 99%